PENGARUH TAYANGAN MATA NAJWA TERHADAP MINAT BERPOLITIK MAHASISWA FISIP UKI - Sinambela, Nova Betriani (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2021)
Abstract The Mata Najwa program broadcast on TV is an educational program and has become quite a topic of discussion, this is because the program has a theme that is closely related to social and political issues and is reviewed sharply and thoroughly so that people who watch it get new information that is rarely published. The Mata Najwa show also presents another side of politics and the nature of politicians. The issue raised is how the Mata Najwa program can change the interest of young people towards politics so that young people are no longer apathetic to politics. The purpose of this study was to analyze the effect of Mata Najwa’s show on the political interest of the students of the Faculty of Social and Political Sciences, Christian University of Indonesia. Therefore, agenda setting theory is used to frame political issues from the perspective of the Mata Najwa show. The method used in this research is quantitative with a positivism paradigm. The respondents of this study were students of the Faculty of Social and Political Sciences, Christian University of Indonesia with a total population of 785. The results of this study indicate the effect of the Mata Najwa program on FISIP UKI students. Keywords: Mata Najwa Show, College Student Tayangan Mata Najwa yang disiarkan di TV merupakan tayangan mendidik dan cukup banyak menjadi perbincangan, hal tersebut dikarenakan acara ini mengangkat tema yang lekat dengan masalah sosial dan politik dan diulas dengan tajam dan seksama sehingga masyarakat yang menonton memperoleh informasi baru yang jarang terpublikasikan. Tayangan Mata Najwa ini juga menyuguhkan sisi lain politik dan sifat politisi. Masalah yang diangkat adalah bagaimana acara Mata Najwa mampu mengubah minat anak muda terhadap politik sehingga anak muda tidak lagi apatis terhadap politik. Tujuan dari penelitian ini adalah untuk melihat seberapa besar pengaruh tayangan Mata Najwa terhadap minat berpolitik mahasiswa Fakultas Ilmu Sosial dan Politik Universitas Kristen Indonesia. Oleh sebab itu digunakan teori agenda setting untuk membingkai isu politik dari perspektif acara Mata Najwa. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan paradigma positivisme. Responden penelitian ini adalah mahasiswa/i Fakultas Ilmu Sosial dan Politik Universitas Kristen Indonesia dengan total populasi sebanyak 785. Hasil penelitian ini menunjukan adanya pengaruh acara Mata Najwa terhadap mahasiswa FISIP UKI. Keywords: Tayangan Mata Najwa, Mahasiswa